ANALISIS PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP AGRESIVITAS PAJAK - Winarti Monika Sagala; Dwi Ratmono (Diponegoro Journal of Accounting, 2015)
The aim of this study is to examine the effect of disclosure of Corporate Social Responsibility (CSR) to  corporate tax aggressiveness. The independent variable is  used  in this study is  corporate  social  responsibility  disclosure.While  the  dependent  variable  in  this study is tax aggressiveness that measured using proxy Effective Tax Rates (ETR). This study  is a replication of the  study by  Lanis and  Richardson  (2012)  and use 375 non-financial companies that  listed  on the  Indonesia  Stock Exchange  in  the period  2011-2013  as  the  sample.  Samples  were  selected  by  probability  sampling method  and  finally  obtained  125  non-financial  companies that  fulfill  the criterias. Data were analyzed using ordinary least square regression analysis model.The result  shows  that the  higher the level of CSR disclosure of a corporation, the lower is the level of tax aggressiveness. This result support the theory of legitimacy.